2014
DOI: 10.1017/s0021859614000525
|View full text |Cite
|
Sign up to set email alerts
|

Iron and zinc concentrations in peanut (Arachis hypogaeaL.) seeds and their relationship with other nutritional and yield parameters

Abstract: SUMMARYBiofortification (delivery of micronutrients via micronutrient-dense crops) can be achieved through plant breeding and offers a cost-effective and sustainable approach to fighting micronutrient malnutrition. The present study was conducted to facilitate the initiation of a breeding programme to improve the concentration of iron (Fe) and zinc (Zn) in peanut (Arachis hypogaea L.) seeds. The experiment was conducted with 64 diverse peanut genotypes for 2 years in eight different environments at the Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…ICGV 00351 was released in India as a drought-tolerant variety [48], and ICGV 00350 and TAG 24 were released for post-rainy season cultivation in Zone 5 of India. ICGVs 06040 and 06099 were identified as high kernel Fe-and Zn-containing lines [49], and ICGVs 05155, 06420, 03057 and 03042 are high oil containing lines now in national level multi-location testing in India under the All India Coordinated Research Project on Groundnut.…”
Section: Heat-tolerant and Superior Pod-yielding Groundnut Genotypesmentioning
confidence: 99%
“…ICGV 00351 was released in India as a drought-tolerant variety [48], and ICGV 00350 and TAG 24 were released for post-rainy season cultivation in Zone 5 of India. ICGVs 06040 and 06099 were identified as high kernel Fe-and Zn-containing lines [49], and ICGVs 05155, 06420, 03057 and 03042 are high oil containing lines now in national level multi-location testing in India under the All India Coordinated Research Project on Groundnut.…”
Section: Heat-tolerant and Superior Pod-yielding Groundnut Genotypesmentioning
confidence: 99%
“…Disease score for LLS is associated with component traits of resistance consequently, disease scores in the field suffice to evaluate the breeding material for resistance to LLS. Absence of trade-off between oil content and yield (Janila et al, 2014 ) enabled development of high oil yielding breeding lines. Back cross breeding was rarely used because most of the desired economic traits in groundnut are quantitatively inherited.…”
Section: Groundnut Improvement Using Conventional Breeding Methodsmentioning
confidence: 99%
“…Breeding for high oleic groundnut began with the discovery of F435 a high oleic acid spontaneous mutant with an oleic acid content of >80% (Norden et al, 1987 ), and the first high oleic variety, SunOleic 95R with 82% oleic acid content was registered in 1997 (Gorbet and Knauft, 1997 ). ICGV 03137, a Virginia bunch variety with high blanchability (Janila et al, 2012 ) and ICGV 06099 and ICGV 06040 with high kernel Fe and Zn (Janila et al, 2014 ) were reported. Large seeded varieties, preferred for table purposes, such as Asha and Namnama were released in Philippines and Mallika was released in India.…”
Section: Groundnut Improvement Using Conventional Breeding Methodsmentioning
confidence: 99%
“…To add more to the health benefit of groundnut, improvement for nutritional traits, i.e. biofortification, such as iron and zinc must be on the breeding agenda [106,113]. This is important to reduce the prevalence of anaemia among preschool-age children (≥40%) [110].…”
Section: Exploring Novel Industrial Uses Of Groundnutsmentioning
confidence: 99%